2008
DOI: 10.7863/jum.2008.27.7.1041
|View full text |Cite
|
Sign up to set email alerts
|

Three- and 4-Dimensional Ultrasonography in the Prenatal Evaluation of Fetal Anomalies Associated With Trisomy 18

Abstract: Objective. The purpose of this study was to assess the usefulness of 3-and 4-dimensional ultrasonography (3D/4DUS) for the description of anomalies associated with trisomy 18 and to determine whether 3D/4DUS adds diagnostic information over what is provided by conventional 2-dimensional ultrasonography (2DUS) alone. Methods. Twenty-six fetuses subsequently proven to have trisomy 18 underwent prenatal ultrasonographic evaluations by both 2DUS and 3D/4DUS. Volume data sets were acquired by the same sonographers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…25,36 Although the potential utility of 3D sonography is broad, prior studies have shown it to be particularly useful for the depiction of certain structures, including fetal limbs. 11,24,26,29,37,38 Sepulveda et al 39 reported a 6% firsttrimester detection rate of abnormal hand posturing in their case series of 55 fetuses with trisomy 18, specifically noting the possibility of 3D sonography improving this low detection rate. Although 3D sonography was only considered useful in 3 of the 9 cases in which it was performed in this study, its utility in characterizing defects and explaining anomalies to parents was considered essential in each of these cases (Figures 1 and 3).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…25,36 Although the potential utility of 3D sonography is broad, prior studies have shown it to be particularly useful for the depiction of certain structures, including fetal limbs. 11,24,26,29,37,38 Sepulveda et al 39 reported a 6% firsttrimester detection rate of abnormal hand posturing in their case series of 55 fetuses with trisomy 18, specifically noting the possibility of 3D sonography improving this low detection rate. Although 3D sonography was only considered useful in 3 of the 9 cases in which it was performed in this study, its utility in characterizing defects and explaining anomalies to parents was considered essential in each of these cases (Figures 1 and 3).…”
Section: Discussionmentioning
confidence: 98%
“…Three‐dimensional depiction of the developing fetus has also been shown to be more comprehensible to lay people, which can be useful when counseling parents about detected anomalies 25 , 36 . Although the potential utility of 3D sonography is broad, prior studies have shown it to be particularly useful for the depiction of certain structures, including fetal limbs 11 , 24 , 26 , 29 , 37 , 38 . Sepulveda et al 39 reported a 6% first‐trimester detection rate of abnormal hand posturing in their case series of 55 fetuses with trisomy 18, specifically noting the possibility of 3D sonography improving this low detection rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations